Control of Leg Movements Driven by EMG Activity of Shoulder Muscles - La Scaleia, Valentina; Sylos-Labini, Francesca; Hoellinger, Thomas; Wang, Letian; Cheron, Guy; Lacquaniti, Francesco; Ivanenko, Yuri P. (Frontiers in Human Neuroscience, 2014)
During human walking there exists a functional neural coupling between arms and legs, and between cervical and lumbosacral pattern generators. Here we present a novel approach for associating the electromyographic (EMG) activity from upper limb muscles with leg kinematics. Our methodology takes advantage of the high involvement of shoulder muscles in most locomotor-related movements and of the natural coordination between arms and legs. Nine healthy subjects were asked to walk at different constant and variable speeds (3-5 km/h), while EMG activity of shoulder (deltoid) muscles and the kinematics of walking were recorded. To ensure a high level of EMG activity in deltoid, the subjects performed slightly larger arm swinging than they usually do. The temporal structure of the burst-like EMG activity was used to predict the spatiotemporal kinematic pattern of the forthcoming step. A comparison of actual and predicted stride leg kinematics showed a high degree of correspondence (r>0.9). This algorithm has been also implemented in pilot experiments for controlling avatar walking in a virtual reality setup and an exoskeleton during overground stepping. The proposed approach may have important implications for the design of human-machine interfaces and neuroprosthetic technologies such as those of assistive lower limb exoskeletons.